PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP PROFITABILITAS DENGAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL INTERVENING - Hutagaol, Dahlia; Hasyim, Diana (STIE Mahardhika, 2024)
2018-2022 period. The motivation for this research stems from a decline in the companies' profit-earning ability, while the influencing factors do not move in tandem. The sampling method used is purposive sampling, with 267 companies selected as the sample for this study. The analysis technique employed is panel data regression analysis using E-views 12 software. The results show that managerial ownership has a negative and significant effect on CSR but no effect on ROA. Institutional ownership does not affect CSR but has a positive and significant effect on ROA. The independent board of commissioners positively and significantly affects CSR but negatively and significantly affects ROA. Furthermore, CSR mediates the effect of managerial ownership and the independent board of commissioners on ROA, but it does not mediate the effect of institutional ownership on ROA.